Growth differentiation factor-15 level predicts major bleeding and cardiovascular events in patients with acute coronary syndromes: results from the PLATO study - Hagström, Emil; Katus, Hugo (European heart journal, 2016)
AbstractAims. Growth differentiation factor-15 (GDF-15) predicts death and composite cardiovascular (CV) events in patients with acute coronary syndrome (ACS).